Ludwig's angina in children anesthesiologist's nightmare: Case series and review of literature - Maitree Pandey; Manpreet Kaur; Manoj Sanwal; Aruna Jain; Sunil K Sinha (Wolters Kluwer Medknow Publications, 2017)
Ludwig's angina is potentially lethal, rapidly spreading cellulitis of the floor of mouth and neck. The anticipated difficult airway becomes even more challenging when it occurs in children. In children, the larynx is positioned relatively higher in the neck, and one does not have the option for blind nasal intubation or awake fiberoptic, which otherwise is the technique of choice in adult patients. We present the clinical course of 16 children and highlight various problems encountered during the anesthetic management of six children who required emergency surgical drainage under general anesthesia.